Design and Construction of a Safe Viewing Distance Detection Tool for Laptop Screens Using the HC-SR04 Ultrasonic Sensor - Afriansyah Putra; Liemalasintasari; Muhamad Mirza Alfarisi (Faculty of Engineering - Universitas Pembangunan Nasional Veteran Jakarta, 2026)
Prolonged laptop use with an excessively close viewing distance can cause eye discomfort, such as dry eyes and visual strain, commonly experienced by students. This article presents the design and development of a laptop monitor safe-distance detection device to assist users in maintaining an appropriate viewing distance. The system utilizes an Arduino Uno R3 microcontroller and an HC-SR04 ultrasonic sensor to measure the distance between the user and the laptop monitor. The measured distance is classified into three conditions: danger, warning, and safe, based on predefined thresholds. Distance information and system status are provided through traffic light LEDs, an LCD with an I2C module, and a buzzer as an alert. Test results indicate that the system is able to detect distance changes accurately and generate appropriate output responses. The device is expected to improve user awareness of proper viewing distance during laptop use.